(untitled) (Swiss Medical Weekly, 2025)
AIM: To prospectively assess varicella zoster virus-associated disease burden in hospitalised children 0–16 years of age prior to the introduction of universal varicella vaccination in Switzerland. METHODS: We performed an observational, prospective surveillance study. Anonymised data (clinical characteristics, diagnostics, treatment and outcome) of hospitalised children were available from monthly active case reporting by 29 paediatric clinics and hospitals to the Swiss Paediatric Surveillance Unit from July 2021 to June 2023. RESULTS: During the 2-year study period, 239 children were hospitalised with varicella (n = 224; 94%) or herpes zoster (n = 15; 6%). Mean age was 5 years, median 4.7 years (range 0–16 years). In 13 patients, varicella was concomitant and not the primary reason for hospitalisation. 199 patients (83%) were primary healthy, 138 were male (58%). Mean duration of hospitalisation for varicella patients was 5.7 days. Of the 224 children with varicella, 211 (94%) were primary hospitalised due to varicella, 120 (54%) had acute skin complications (including 52 Streptococcus pyogenes infections), 29 (13%) musculoskeletal and 27 (12%) neurological complications. Two patients (1%) had ischaemic strokes. 33 (14%) patients (32 with varicella and 1 with herpes zoster) required intensive care treatment (mean duration 3.5 days). 40 patients with varicella (18%) required surgical interventions. Two (1%) patients died. The calculated hospitalisation incidence rate was 7.2 per 100,000 for children and the calculated hospitalisation rate was 12.6 per 10,000 cases. CONCLUSIONS: Varicella is associated with considerable morbidity, particularly in primary healthy children. Complications affecting the skin (mainly secondary bacterial infections), musculoskeletal and neurological systems are the main reasons for hospitalisation and may cause death even in previously healthy, immunocompetent children. The baseline burden of disease presented herein will permit evaluation of the impact of universal varicella vaccination, introduced in Switzerland in January 2023.